2017
DOI: 10.1073/pnas.1700054114
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical feedback underlies coexistence of qualitatively distinct cell polarity patterns within diverse cell populations

Abstract: Cell polarization and directional cell migration can display random, persistent, and oscillatory dynamic patterns. However, it is not clear whether these polarity patterns can be explained by the same underlying regulatory mechanism. Here, we show that random, persistent, and oscillatory migration accompanied by polarization can simultaneously occur in populations of melanoma cells derived from tumors with different degrees of aggressiveness. We demonstrate that all of these patterns and the probabilities of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
118
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
3

Relationship

4
6

Authors

Journals

citations
Cited by 58 publications
(127 citation statements)
references
References 63 publications
(85 reference statements)
8
118
1
Order By: Relevance
“…Recent analysis suggested that these matrix re-arrangements can be well approximated in experiments, using matrix-mimicking nano-fabricated platforms that allow for controlled variation of the model matrix structure and chemical composition [9]. In particular, in our experimental analysis with melanoma cell lines we found that individual cells can display diverse polarity patterns when migrating in areas of the model matrix with various degrees of anisotropy [10]. Having this type of controlled micro-environment can allow one to develop mechanistic models [11] of cell polarity control and to test them by checking for consistency between model predictions and experimental results.…”
Section: Introductionmentioning
confidence: 61%
“…Recent analysis suggested that these matrix re-arrangements can be well approximated in experiments, using matrix-mimicking nano-fabricated platforms that allow for controlled variation of the model matrix structure and chemical composition [9]. In particular, in our experimental analysis with melanoma cell lines we found that individual cells can display diverse polarity patterns when migrating in areas of the model matrix with various degrees of anisotropy [10]. Having this type of controlled micro-environment can allow one to develop mechanistic models [11] of cell polarity control and to test them by checking for consistency between model predictions and experimental results.…”
Section: Introductionmentioning
confidence: 61%
“…Thus, the model offers an explanation for the origin of POP; it is an emergent behavior based on COA and CIL rather than a separate mechanism to be postulated in addition to these two. This hypothesis can be tested by experiments that use drugs to partially suppress various proteins (or their activation levels) in the Rho GTPase signaling pathway [58,59]. The resulting impairment of collective migration can be compared with model predictions of how COA, CIL and POP are affected by modulating the suitable Rac1 and RhoA rate constants.…”
Section: Discussionmentioning
confidence: 99%
“…Rho GTPases are core regulators of mesenchymal and amoeboid cell migration. They integrate multiple internal and external cues (Campa et al, 2015;Devreotes et al, 2017;Lin et al, 2015;Park et al, 2017;Park et al, 2019) and relay information to a variety of cellular protein machineries, including proteins driving actin polymerization and cytoskeleton rearrangements, thereby enabling cell migration (Warner et al, 2019). Although molecular details of Rho GTPaseeffector interactions have been elaborated, we still lack an overall picture of how these GTPase activities and effector interactions are coordinated between the leading and trailing edge in order to enable cell movement.…”
Section: Discussionmentioning
confidence: 99%